2004
DOI: 10.1111/j.1365-2788.2003.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking prevalence and knowledge of associated risks in adult attenders at day centres for people with learning disabilities

Abstract: The study provides no evidence that rates of smoking are increasing among people with learning disabilities nor that those living independently were more likely to smoke. Knowledge of health risks is poor across the group, but higher among the smokers who were unlikely to express concern about the risks. This may indicate that more support may be needed along with health education in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
2
24
1
2
Order By: Relevance
“…Previous research found a lower prevalence of smoking among individuals with ID than in the general population (Fakier & Wild, 2011;Gress & Boss, 1996;McGillicuddy & Blane, 1999;McGuire et al, 2007;Rimmer et al, 1995;Robertson et al, 2000;Rurangirwa et al, 2006;Taylor et al, 2004). In contrast, Emerson and Turnbull (2005) found that the prevalence of smoking was higher among adolescents with ID.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Previous research found a lower prevalence of smoking among individuals with ID than in the general population (Fakier & Wild, 2011;Gress & Boss, 1996;McGillicuddy & Blane, 1999;McGuire et al, 2007;Rimmer et al, 1995;Robertson et al, 2000;Rurangirwa et al, 2006;Taylor et al, 2004). In contrast, Emerson and Turnbull (2005) found that the prevalence of smoking was higher among adolescents with ID.…”
Section: Introductionmentioning
confidence: 69%
“…The prevalence of alcohol drinking was higher in residents of group homes and lower in residents of institutions compared with those living with their families. Taylor et al (2004) reported a lower prevalence of smoking in individuals with ID living with their parents in comparison with those living independently and in hospital and staffed housing. Taggart et al (2006) found that a higher percentage of participants with ID and drug use problems lived with their families than in supported living schemes and residential facilities.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…As to SU, in a Belgian study in 123 individuals with MBID living independently, 48% smoked, 46% drank alcohol, and 2% used illicit substances in the past month (Swerts et al 2017). Smoking rates in other community based samples of adults with ID, were much lower, for instance 1.9% in social education centers (Whitaker and Hughes 2003), and 9.3% in attenders at day care centers (Taylor et al 2004). In adolescents with MBID, however, current smoking rates varied from 14% (Emerson and Turnbull 2005) to 34% (Žunić-Pavlović et al 2013) and in forensic ID samples smoking rates are reported to be up to 60% (Chester et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…It is commonly acknowledged that people with intellectual disability have a wide range of health problems (Cooper et al, 2004;Emerson et al, 2009). Compared with the general population, there is a higher prevalence rate of both psychological disorders (Deb et al, 2001;Taylor et al, 2004) and (untreated) physical disorders (Emerson and Baines, 2010;Leeder and Dominello, 2005). People with intellectual disability are often granted a 'permanent visa to the kingdom of the sick', as intellectual disability is often equated with ill health (Tighe, 2001, p. 511).…”
Section: Introductionmentioning
confidence: 99%